1998
DOI: 10.1111/1468-0009.00087
|View full text |Cite
|
Sign up to set email alerts
|

The Use of EPSDT and Other Health Care Services by Children Enrolled in Medicaid: The Impact of OBRA'89

Abstract: To increase the participation of Medicaid children in the Early and Periodic Screening, Diagnosis and Treatment (EPSDT) program and to improve their health, Congress included several provisions in the Omnibus Budget Reconciliation Act of 1989 (OBRA’89) that addressed problematic program features. The impact of these provisions on children's health service use was investigated in a study funded by the Health Care Financing Administration. After conducting site visits to four states, the authors analyzed claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…[28][29][30] The American Academy of Pediatrics (AAP) recommends 6 EPSDT visits in the first year of life and 3 in the second year. 31,32 These recommendations have been endorsed by the South Carolina Department of Health and Human Services for infants who are enrolled in Medicaid. The number of infant EPSDT visits represents the combined number of visits for immunizations and/or screening services.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…[28][29][30] The American Academy of Pediatrics (AAP) recommends 6 EPSDT visits in the first year of life and 3 in the second year. 31,32 These recommendations have been endorsed by the South Carolina Department of Health and Human Services for infants who are enrolled in Medicaid. The number of infant EPSDT visits represents the combined number of visits for immunizations and/or screening services.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Even while PCCM is intended to reduce unnecessary utilization, and perhaps primary care, it is not intended to reduce preventive care among these low-income children as these services are generally underused (Gavin et al 1998). Our analysis indicates, however, that PCCM reduced the odds of receiving preventive care both through its direct effect and through any related changes in provider availability in the urban areas of Alabama for white and black non-Hispanic children and in Georgia, only for urban black children.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of PCCM found clear effects in terms of the use of the emergency room (ER), prescription drugs, and hospital services (Hurley, Freund, and Paul 1993) but less specific findings with regard to preventive care (Hurley, Freund, and Paul 1993;Gavin et al 1998;Zuckerman, Brennan, and Yemane 2002). By and large, these studies did not address possible differential effects of PCCM on children from different racial/ethnic backgrounds on utilization.…”
Section: New Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the intervening years, programs have been aimed at improving preventive care of lower income children. 69,70 A Centers for Disease Control and Prevention (CDC) study of children born from 1993 to 1995 showed improved immunization levels, in spite of an increased number of required immunizations, but there were continuing racial disparities among the poor. 71 Improved immunization rates are no guarantee of improved preventive care rates unless immunization is consistently provided in the context of a preventive care visit.…”
Section: Discussionmentioning
confidence: 99%